Refugia effect on arthropods in an organic paddy field in Malang District, East Java, Indonesia - Zainal Abidin Suyono; AMIN SETYO LEKSONO; BAGYO YANUWIADI; MANGKU PURNOMO (Society for Indonesian Biodiversity, 2020)
Abstract. Abidin Z, Leksono AS, Yanuwiadi B, Purnomo M. 2020. Refugia effect toward arthropods in an organic paddy field in Malang District, East Java, Indonesia. Biodiversitas 21: 1415-1421. This study aims to determine the abundance, community structure, and diversity of arthropod visitors of refugia in organic paddy fields in the Malang District of East Java, Indonesia. This research was conducted in 2019 from February to June and covered the stages from planting to harvest. The paddy fields were divided into 12 plots consisting of six refugia plots and six control plots. Sampling was carried out in two five-day phases, specifically in the vegetative phase (February) and the generative phase (June) of paddy plants. The results showed that 28.184 species consisting of nine orders and 40 families were observed. The abundance of common predator families, such as the Aleyrodidae, Formicidae, Libellulidae, and Tetragnatidae, in organic paddy. The average arthropod taxa richness in the refugia was 20.59 ± 12.24 species, while in the control it was 13.16 ± 8.95 species. Statistical analysis showed that the difference was significant (p < 0.05). The average arthropod diversity in the refugia was 2.39 ± 0.78 species, while in control was 2.35 ± 0.15 species. In conclusion, the population of arthropods was the highest in the refugia. Therefore, organic paddy surrounded by refugia with wild plants was the most appropriate habitat and niche for predatory arthropods.